Metabolizable energy and net energy content of corn, wheat bran, soybean meal, fish meal and soybean oil for broilers - Moscoso-Muñoz, Juan (2020)
A study was carried out to determine the metabolizable energy (ME) and net energy (NE) of corn, wheat by-product, soybean meal, fishmeal, and soybean oil in poultry. 190 male chickens were used, distributed in six experimental diets (basal (B), B + corn (40%), B + wheat by-product (40%), B + soybean meal (30%), B + fish meal (30%), B + soybean oil (10%) with three feeding levels (ad libitum (AL), 85% AL and 70% AL). ME was determined by the total collection method of excreta and NE by the comparative slaughter method, the chickens received the experimental diets from 7 to 21 days of age, the excreta were collected every 24 hours (day 19 to 21). For NE, the energy retained and heat production were determined (7 and 21 days) The ME and NE of corn, wheat by-product, soybean meal, fishmeal and soybean oil was 3734, 2197, 2477, 3289, 8767 kcal / kg DM and 2527, 1598, 1417, 1837, 7550 kcal / kg DM respectively, the NE: ME ratio was higher with soybean oil compared to other feed ingredients.